Gosip Dalam Al-Qur’an Perspektif Tafsir Al-Mishbah dan Implementasinya Terhadap Kehidupan Muslim Kontemporer - Al Khikma Aulia Karim; Muhamad Amrullah; Murdiyanto Murdiyanto (Yayasan Sembilan Pemuda Indonesia, 2026)
Gossip is a form of communication that is prohibited in the Qur’an, yet it is rampant in the digital age. This study aims to analyze the verses of the Qur’an regarding gossip through the perspective of Tafsir Al-Mishbah by M. Quraish Shihab and to examine its implementation in the lives of contemporary Muslims. This study employs a qualitative literature review method with a thematic and descriptive-analytical approach. The findings reveal that Quraish Shihab offers a contextual and practical interpretation of the verses on gossip, emphasizing the importance of guarding one’s speech, seeking clarification, and avoiding backbiting, particularly in digital communication. This study affirms that a contextual interpretation approach can address the ethical issues of communication among contemporary Muslims and serve as a solution for building a more ethical, healthy, and Islam-compliant communication culture. The novelty of this research lies in the integration of the contextual interpretation of Al-Mishbah with the problems of digital communication, as well as providing practical impacts for the development of Islamic communication ethics in the digital era.